KARAKTERISTIK MORFOLOGI BATANG DAN DAUN PADA 14 GENOTIPE PADI LOKAL (Oryza sativa. L) KABUPATEN KUANTAN SINGINGI - Rendi Irawan; Chairil Ezward; Sepridho Sepridho (University of Prof. Dr. Hazairin, SH, 2020)
Characterization is an observation process with the aim of knowing the characteristics of a plant. The aims of the study is to identify and characterize 14 genotypes local rice in Kuantan Singingi Regency. This research was used purposive sampling method (purposive random sampling). Data were collected by identifying the characteristics of 14 genotypes local rice in Kuantan Singingi directly into the field. Data observations were carried out on samples based on the guidelines for the characterization and evaluation system for rice plants, the National Commission for Germplasm (2003) and Bioversity International, IRRI and WARDA (2007). The characters observed were qualitative and quantitative characters in the stem and leaf organs. Observation data were processed using Ms. software. Excel and (NTSYS-pc) version 2.02. The results showed a variety of morphological characters of stems and leaves, where the 79% similarity coefficient resulted in five (5) groups.